Keefektifan Poly Alumunium Chloride (PAC) Dalam Menurunkan Kadar Bod (Biological Oxygen Demand) Pada Limbah Cair Industri Batik Desa Kliwonan Masaran Sragen - FITRIANA, Wiwin (2016)
BOD (Biological Oxygen Demand) in Waste Water Treatment Plant (WWTP) Kliwonan Masaran Sragen batik village has exceeded the quality standard that 319.58 mg / l. According to the Central Java Provincial Regulation No. 5 of 2012 on the Amendment of Central Java Provincial Regulation No. 10 of 2004 on Wastewater Quality Standard Textile and Batik is 60 mg / l. The purpose of this study to determine the effectiveness of the PAC in lowering levels of BOD in the industrial wastewater in the village Kliwonan Masaran batik Sragen. This research method True Experiment with pretest and posttest study design with Control Group. Processing using Poly Aluminum Chloride (PAC) at a dose of 0 g / l; 1,5 gr / l; 3 g / l; 4,5 g / l; and 6 g / l with a quick manual method of stirring 100 rpm for 1 minute, 20 rpm for 15 minutes and precipitation for 30 minutes. The population in this study is the WWTP effluent outlet village Kliwonan Masaran Sragen batik produced from the whole process of making batik is collected and processed in WWTP. The number of samples taken is 30 liters with the technique of taking the sample size is determined by the Quota sampling techniques. ANOVA statistical test using one path obtained significance value of 0.000 (p <0.01), showed no difference between the reduction in BOD levels before and after treatment in wastewater Kliwonan Masaran Sragen batik village. PAC coagulant dosage is most effective at lowering levels of BOD in the wastewater industry Kliwonan Masaran Sragen batik village is 6 g / l.